Engage : a guide to creating life-transforming worship services - Searcy, Nelson; Hatley, Jason; Henson, Jennifer Dykes (Grand Rapids, Mich. : Baker Books, 2011)
Offers step-by-step instructions on planning creative Sunday worship services that combine the efforts of pastors, volunteers, and worship leaders.
Why ask why? : determining your philosophy of worship -- Worship : seven principles of life-transforming worship -- Wanted : radically transformed lives -- Laying a solid foundation : how to plan your preaching -- Preaching for life transformation : tips and temptations -- Below the waterline : building your worship planning system -- Creative transformation : aligning creative elements for excellence -- The trial run : conducting a message run-through -- Defining relationships : the pastor/worship pastor challenge -- Evaluating for excellence : the philosophy behind service evaluation -- Closing the book : how to evaluate and improve your services -- Conclusion: Five steps to more engaging worship next Sunday.
Includes bibliographical references.
Keywords: Public worship -- Planning